Sparing Lives : Better Reproductive Health for Poor Women in South Asia, Summary for Policymakers - Chatterjee, Meera; Levine, Ruth; Murthy, Nirmala; Rao-Seshadri, Shreelata (New Delhi: Macmillan India, Ltd., 2012)
In this context, the overall purpose of this review is to bring attention to the opportunities that five countries in the region - Bangladesh, India, Nepal, Pakistan and Sri Lanka - have to strengthen and expand interventions to improve the reproductive health of poor women. The specific objectives are: i) to provide an accurate picture of the current status of women's reproductive health, describe the use of reproductive health services and barriers to use, and identify the improvements required to increase their effectiveness and improve health outcomes; ii) to elucidate individual and household characteristics that affect reproductive health status and use of services so that the most important of these can be used to identify women and households with the greatest need for care to achieve better health; iii) to describe a simple and effective approach - decentralized action planning - that can be used widely in all five countries to improve reproductive health service delivery and outcomes, and point to a body of best practices in reproductive health that provides models and lessons for improvements in South Asia; and iv) to strengthen the case for investing in poor women's reproductive health by demonstrating the links between poverty, inequality, reproductive health care and expenditure.